ONLINE LEARNING ANALYSIS OF STUDENTS' LEARNING INTEREST IN SD MUHAMMADIYAH 11 SURABAYA - Eka Novita Sari; Badruli Martati; Lilik Binti Mirnawati (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research is to know the interest of students in distance learning in grade I of SD Muhammadiyah 11 Surabaya. The type of research used is qualitative research. Participants in the study were teachers, grade 1 students and parents with data collection techniques conducted, namely questionnaires, interviews, and documents. The results showed that students' interest in learning while participating in distance learning based on high achievement criteria is good enough because students enjoy learning, so they always actively ask their parents if they do not understand. The interest in learning students with moderate achievement criteria is also good enough because students are happy with the assistance from parents so that students show seriousness in learning. While students with achievement criteria are lacking, their learning interest is still lacking, this is due to the background of working parents.